Islam, Ethnicity and Cultural Politics of Identity: The religiousity of Betawi Muslim in Jakarta - Deni Miharja; M. Mulyana; Ahmad Izzan (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2019)
Betawi is an ethnic group that is considered a native of Jakarta, the capital city of Indonesia. There have been efforts to strengthen Islamic identity in defining Betawi after the reformation era in 1998. This article focuses on the religious expression of Betawian Muslims and the strengthening of local cultural identity in Jakarta, using a phenomenological study and theory of identity. This study shows that the strengthening religious identity of Betawian Muslims is reflected in various dynamics of religious understanding, the politicization of ritual practices and the emergence of new religious groups among Betawian Muslims, such as the FBR, Majelis Rasulullah and the other. These various religious experiences increasingly strengthening the politics of identity to foreground Islamic identity in defining Betawian. It is a cultural identity that is narrow and different from the hybrid Betawi culture that was historically shaped by ethnic and religious diversity in the cosmopolitan cultural space.